Between Post-Racial Ideology and Provincial Universalisms: Critical Race Theory, Decolonial Thought and COVID-19 in Britain. (February 2022) - Meghji, Ali; Niang, Sophie Marie
This article looks at the British government's handling of the first wave of the coronavirus pandemic. We argue that to analyse the government's handling of this situation, we need to synergize insights from critical race theory (CRT) with decolonial thought. CRT shows how the pandemic has revealed and exacerbated racial inequalities within Britain, while these inequalities are then explained away through a post-racial ideology. Contrastingly, decolonial thought helps us to understand how Britain practises western and little Englander universalisms; neglecting other countries' successful strategies of handling the pandemic, as they seek to pursue a 'world-beating' strategy to defeat the virus rather than help forge a global solidarity.